Implementasi Perencanaan Strategis Dalam Meningkatkan Mutu Pendidikan SMP Negeri 1 Bengalon Kutai Timur - Ridwan Ridwan; Zaenab Hanim; Murni Murni; Misnawati Misnawati (Journal on Education, 2023)
Indonesian education has challenges in producing quality graduates with excellent personalities. In solving this problem, schools can implement strategies to improve the quality of their education by implementing strategic planning. This study aims to: 1) analyze the preparation of strategic planning, 2) analyze the strategic planning implementation strategy, 3) analyze the evaluation and implications of the implementation of strategic planning on the quality of education in SMP Negeri 1 Bengalon. The research used a qualitative approach and collected data using interview, observation and documentation techniques. The results of the research show: First, the preparation of strategic planning through 2 stages: a) analysis of the internal and external environment; b) strategy formulation. Second, strategic planning implementation techniques: a) involving stakeholders; b) maximizing available resources. Third, a) internal and external evaluation by evaluating teaching and learning processes and outcomes, evaluating graduates, looking at teacher professionalism, evaluating achievement, monitoring by education supervisors and accreditation by BAN; b) the implication, experiencing an increase in the quality of education with indicators: improvement in the teaching and learning process, achievement, number of students, increasing the percentage of graduates, and fulfillment of supporting facilities for the learning process in accordance with the SNP